61.2k views
2 votes
Simplify the expression 4(2x - 3y) ASAP

User Ariele
by
5.2k points

2 Answers

4 votes

Answer:

8x - 12y

Explanation:

4(2x-3y)

Distribute/multiply the 4 to everything in the parentheses

4 * 2x = 8x 4 * -3y = -12y

8x - 12y

User Ivan Mamontov
by
5.4k points
4 votes

Answer:


4(2x-3y)=8x-12y

Explanation:

The given expression is


4(2x-3y)

We expand using the distributive property to obtain;


4(2x-3y)=4*2x-4*3y

This implies that;


4(2x-3y)=8x-12y

User Jony Kale
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.